Time - Ridderbos, Katinka, 1970- (Darwin College lectures., 2002)
Eminent researchers in fields ranging from the arts and humanities to the natural sciences discuss the subject of time. Asking questions such as 'is it possible to travel in time?' and 'how do biological clocks work?', these essays are written in a clear style accessible to the educated general reader.